Methods of Fighting the Apple Worm - Mardonayeva Dilsora Norkhonovna; Saparova Zulkhumor Zakir's quzi; Razzakova Shokhsanam Kozimorod quzi (Scientific Trends, 2022)
In this article, agrotechnical-mechanical methods are important in combating the apple worm, including: the use of "deceptive belts", the most effective method of combating the apple worm is the effectiveness of the chemical method, the most optimal periods of chemical control against the apple worm, Termiz district against 1st generation worms from the 2nd to ten days of April to May It is reported that it is from the first ten days of May to the first ten days of June
Keywords: Apple worm